Morphology and properties of poly(Lactic acid)/ethylene-octene copolymer nanocomposites - Wacharawichanant, Sirirat; Sriwattana, Attachai; Yaisoon, Kulaya; Phankokkruad, Manop (My University, 2019)
The effects of the montmorillonite clay surface modified with 0.5-5 wt% aminopropyltriethoxysilane and 15-35% octadecylamine (Clay-APTSO) on morphology, mechanical and thermal properties of poly(lactic acid) (PLA)/ethylene-octene copolymer (EOC)/Clay-APTSO composites were investigated. The blends of PLA/EOC with and without Clay-APTSO were prepared by melt mixing in an internal mixer. Scanning electron microscopy analysis observed the morphology of PLA/EOC blends demonstrated a phase separation of minor phase and matrix phase. The addition of Clay-APTSO in PLA/EOC blends showed significant decreased in droplet size of dispersed EOC phase, thus, Clay-APTSO acted as an effective compatibilizer in the PLA/EOC blends. The results of tensile properties found the decrease of Young’s modulus of PLA when added EOC due to the low modulus and flexibility of EOC. While the incorporation of Clay-APTSO increased significantly Young’s modulus of PLA/EOC blends at low EOC and Clay-APTSO content. The strain at break of the blends increased with the increase of EOC loading, this indicated the presence of EOC enhanced the elongation at break of PLA, while the addition Clay-APTSO reduced the strain at break of PLA/EOC blends. The tensile strength of all blend compositions improved when added Clay-APTSO and the tensile strength showed the highest value at 3 phr of Clay-APTSO. The thermal stability of PLA/EOC blends did not change when compared with neat PLA, and when added Clay-APTSO in the blends could improve the thermal stability of the PLA/EOC blends.
Keywords: Ethylene-octene copolymer; Organoclay; Polymer composites; Poy(lactic acid)